Australian rubella serosurvey 2012–2013: On track for elimination?. Issue 20 (11th May 2018) - Edirisuriya, Chathura; Beard, Frank H.; Hendry, Alexandra J.; Dey, Aditi; Gidding, Heather F.; Hueston, Linda; Dwyer, Dominic E.; Wood, James G.; Macartney, Kristine K.; McIntyre, Peter B.
Abstract: Background: The World Health Organization has targeted rubella virus for elimination regionally. Australia was one of the first countries to implement a nationally funded rubella immunisation program, in 1971, and conducts regular national rubella serosurveillance studies. We aimed to estimate the seroprevalence of rubella-specific IgG antibody in the Australian population by age and sex in 2012–2013, to compare the results with three previous serosurveys conducted in 1996–1999, 2002 and 2007 and to estimate the effective reproduction numbers (Rn ). Methods: This study used 2729 serum and plasma specimens, randomly selected from a specimen bank collected in 2012–2013 across Australia. Age groups included in the sample ranged from 1 to 49 years. Sera were tested for rubella-specific IgG-antibody using the Enzygnost anti-rubella IgG enzyme immunoassay and classified as positive, negative or equivocal according to rubella-specific IgG concentrations of >7 IU/ml, <3 IU/ml and 3–7 IU/ml, respectively. Results: The overall proportions seropositive, seronegative and equivocal for rubella-specific IgG were 92.1% (95% CI, 91.0–93.2), 6.7% (95% CI, 5.7–7.7) and 1.2% (95% CI, 0.8–1.6), respectively. The proportion of males seropositive was significantly lower than females in the 30–34 (83.1% vs. 96.8%, p = 0.003), 35–39 (86.1% vs. 96.3%, p = 0.02) and 40–44 (86.1% vs. 95.7%, p = 0.03) year age groups. Rn for rubella in 2012–2013 was estimated to be 0.33 (95% CI 0.28–0.39). Discussion: The 2012–2013 national serosurvey showed levels of rubella-specific IgG seropositivity in the Australian population are relatively high with no evidence of decrease compared to previous serosurveys conducted in 1996–1999, 2002 and 2007. The lower proportion of seropositive males aged 30–44 years likely reflects the initial immunisation program targeting females only. To our knowledge this study represents the longest period of serosurveillance following introduction of a nationally funded rubella immunisation program. The lack of evidence of decreasing rubella-specific IgG seropositivity is therefore reassuring for Australia and other countries with longstanding high vaccine coverage.